METHOD CLUSTERING A SEQUENCE OF TRANSFORMANTS BY STRUCTURAL FEATURES THEIR SPECTRAL-PARAMETRIC DESCRIPTION - Barannik, Vladimir; Yeliseev , Evgeny; Tsimura, Yurii; Babenko, Mykhailo; Tarasenko, Denys (Science-based technologies, 2024)
The article substantiates that wireless technological concepts increasingly occupy a key role in modern information and telecommunication systems (ITS). Accordingly, the issue of ensuring the processes of information exchange and decision-making in the management systems of strategically important industries and enterprises is brought to a new level. At the same time, there is a tendency to increase the requirements for the quality of information services. The practical application of IT systems indicates insufficient characteristics in terms of their performance in relation to trends in the provision of video information services. Under such conditions, there is a contradiction between the existing possibilities of ensuring the characteristics of information services and their required level in the conditions of implementation on modern wireless IT systems. The direction of solving this contradiction is based on improving methods to reduce the intensity of video traffic that is processed and transmitted over wireless IT systems. Modern methods of compression of video information streams use platforms that are based on the encoding of transformed video fragments (VF). One of the proven directions here is the formation of a spectral-parametric description of transformants (SPDT). Accordingly, it is necessary to determine the features of this approach in terms of the effectiveness of eliminating the amount of redundancy and reducing the bit volume of video images. One of these technological solutions is the use of clustering methods to identify areas of homogeneity. Hence, the purpose of the article is to develop a method for clustering fragments of frames in their stream, which are previously presented in the spectral-parametric description. A method of clustering a sequence of transformants according to the structural feature of their spectral-parametric description has been developed. The basic feature of the method is the grouping of transformants into clusters by the number of spectral sub-bands in their spot representation. At the same time, the number of computing operations is reduced to two comparison operations regarding the certainty of belonging of the SPDT parameters to a certain interval. Accordingly, conditions are provided for the exclusion of the amount of inter-transformant redundancy in their spectral-parametric description.